Abattoir Effluent and Quality of Water in Nyanchabo Stream, Kisii County, Kenya. - Odhiambo, George Omondi; Gathuru, Gladys (International Journal of Scientific Research and Innovative Studies, 2026)
The existence of livestock in the great expanse of the world’s ecologies affects biodiversity in both developed and fast developing countries where it is frequently a major cause of water pollution. Dairy farm waste and wash-down from slaughter houses constitutes an enormous challenge leading to the release of raw or inadequately treated effluent into water bodies that leads to quality deterioration in receiving waters. Through water quality monitoring, this study aimed to evaluate the impact of Itibo abattoir wastewater on the physico-chemical and bacteriological quality of Nyanchabo stream waters. It ascertained parameters levels of abattoir effluent and stream water before and after the two interacted and compared with the guidelines provided by the National Environmental Management Authority (NEMA) and World Health Organization (WHO). Field sampling was conducted over a six-weeks period, and water quality parameters of temperature, Potential for Hydrogen (pH), Electrical Conductivity (EC), Total Dissolved Solids (TDS), Dissolved Oxygen (DO), Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Nitrate (NO2), Phosphate (PO4) and total coliform, Escherichia coli and Faecal streptococci load were quantified. Standard methods and instruments were employed at the field and laboratory for sample collection and analysis. Statistical analysis was performed using Graph Pad Prism, version 5.0, with statistical significance level set at P<0.05. The study findings revealed that, except for pH, Temperature, EC, DO, TDS and NO2 which got elevated, the abattoir effluent also amplified the levels of TSS (1144±360.8)mg/l, BOD (199.8±47.9)mg/l, COD (2194±1344)mg/l, PO4(12.40±2.725)mg/l, Total coliform (68,183±16,715)cfu/100ml, E. coli (29850±13212) cfu/100ml and F. streptococci (122667±33193)cfu/100ml in the stream waters beyond permissible limits consequently impacting negatively on the stream water quality. Nyanchabo stream water was hence found to be unfit for use by humans and animals unless the effluent was adequately treated before discharge. Additionally, upstream pollution control measures which include soil erosion control, proper disposal of human and animal faecal matter and reclaiming of the riparian land was recommended to avert stream pollution from other non-point sources. Key words: Abattoir wastes, Effluent, Stream, Treatment pond, Water Quality. Received Date: December 20, 2025 Accepted Date: January 12, 2026 Published Date: February 01, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/555